PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER BERBANTUAN WORKSHEET UNTUK MATERI TURUNAN FUNGSI ALJABAR DI SMA/MA - Ayu Anggraini; Armis Armis; Titi Solfitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aims to develop computer-based learning media assisted by worksheet for derivative of algebra function. Development model using 4D model by Thiagarajan,et al there are (1) Define; (2) Design; (3) Develop; and (4) Disseminate. This research is limited to develop stage. On define stage, researcher make need analysis, on design stage make the paper based design, and on develop stage, media made by using Microsoft Office Power Point, then validated by four validators and revised based on validator's suggestion. Media was tested at two steps in class XI SMAN 8 Pekanbaru, there are small group test with six students and large group test with class XI MIA 10. Based on the results of data analysis obtained the result validation of media is 3,65 means very valid with the details are 3,56 for material aspect, 3,83 for learning aspect, 3,68 for program aspect, and 3,62 for display aspect, whereas for worksheet is 3,66 means very valid. Based on students questionnaire obtained the percentage of practicallity is 95,83% means very practice in small group test with the details 100% for material aspect, 97,2% for learning aspect, 91,67% for program aspect, and 91,67% language aspect. On the large group test obtained 94,25% means very practice with details are 92% for material aspect, 95,3% for learning aspect, 92% for program aspect, and 100% for language aspect. It can be concluded that computer-based learning media assisted by worksheet for derivative of algebra function are very valid and very practice for every aspects.Key Words: Computer-Based Learning, Research and Development, Derivative of Algebra Function.